CI Therapy is Beneficial to Patients with Chronic Low-Functioning Hemiparesis after Stroke - Sterr, Annette; O’Neill, Darragh; Dean, Philip J. A.; Herron, Katherine A. (Frontiers in Neurology, 2014)
CI therapy is effective in patients with relatively good levels of residual arm function but its applicability to patients with low functioning hemiparesis is not entirely clear. In the present study we examined the feasibility and efficacy of the CI therapy concept in patients with very limited upper arm function prior to treatment, and further tested how the length of daily shaping training and constraining the good arm affects treatment outcome. In a baseline-controlled design, 65 chronic patients were treated with 2 weeks of modified CI therapy. Patients were randomly allocated to four treatment groups receiving 90 or 180 minutes of daily shaping training applied with or without constraint respectively. Outcome was measured through the Reliable Change Index, which was calculated for parameters of motor function, health and psychological wellbeing. Follow-up data were collected at 6 and 12 months. Two analyses were conducted, a whole-group analysis across all 65 participants and a subgroup analysis contrasting the four treatment variants. The whole-group analysis showed a significant treatment effect, which was largely sustained after one year. The subgroup analysis revealed a mixed picture: while improvements against the baseline period were observed in all four subgroups, 180 minutes of daily shaping training coupled with the constraint yielded better outcome on the MAL but not the WMFT, while for 90 minutes of training the level of improvement was similar for those who wore the constraint and those who did not. Together these results suggest that, at least in those patients available for follow up measures, modified CI therapy induces sustained improvements in motor function in patients with chronic low-functioning hemiparesis. The absence of clear differences between the four treatment variants points to a complex relationship between the length of daily shaping training and the constraint in this patient group which is likely to be mediated by fatigue and